Azathioprine, Mercaptopurine, and 5-Aminosalicylic Acid Affect the Growth of IBD-Associated Campylobacter Species and Other Enteric Microbes - Liu, Fang; Ma, Rena; Riordan, Stephen M.; Grimm, Michael C.; Liu, Lu; Wang, Yiming; Zhang, Li (Frontiers in Microbiology, 2017)
Campylobacter concisus is a bacterium that is associated with inflammatory bowel disease (IBD). Immunosuppressive drugs including azathioprine (AZA) and mercaptopurine (MP), and anti-inflammatory drug such as 5-aminosalicylic acid (5-ASA) are commonly used to treat patients with IBD. This study aimed to examine the effects of AZA, MP and 5-ASA on the growth of IBD-associated bacterial species and to identify bacterial enzymes involved in immunosuppressive drug metabolism. A total of 15 bacterial strains of five species including 11 C. concisus strains, Bacteroides fragilis, Bacteroides vulgatus, Enterococcus faecalis and Escherichia coli were examined. The impact of AZA, MP and 5-ASA on the growth of these bacterial species was examined quantitatively using a plate counting method. The presence of enzymes involved in AZA and MP metabolism in these bacterial species was identified using bioinformatics tools. AZA and MP significantly inhibited the growth of all 11 C. concisus strains. C. concisus strains were more sensitive to AZA than MP. 5-ASA showed inhibitory effects to some C. concisus strains, while it promoted the growth of other C. concisus strains. AZA and MP also significantly inhibited the growth of B. fragilis and B. vulgatus. The growth of E. coli was significantly inhibited by 200 µg/ml of AZA as well as 100 and 200 µg/ml of 5-ASA. Bacterial enzymes related to AZA and MP metabolism were found, which varied in different bacterial species. In conclusion, AZA and MP have inhibitory effects to IBD-associated C. concisus and other enteric microbes, suggesting an additional therapeutic mechanism of these drugs in the treatment of IBD. The strain dependent differential impact of 5-ASA on the growth of C. concisus may also have clinical implication given that in some cases 5-ASA medications were found to cause exacerbations of colitis.